Persepsi Kepuasan Pasien BPJS Kesehatan dan Dimensi Kualitas Pelayanan Rumah Sakit Umum Daerah - Momen Amalia; Christa Bernadeth Ina Tulit; Nursapriani Nursapriani (Journal of Pharmaceutical and Health Research, 2023)
Health service satisfaction is determined by the perception or performance of services in meeting patient expectations. The purpose of this study was to determine the effect of BPJS Kesehatan patients perception on patient satisfaction based on the dimensions of service quality at Labuang Baji Hospital. This research uses quantitative methods with a Cross Sectional Study design. The sample of this study was BPJS Health Patients at Labuang Baji Hospital totaling 87 respondents. Data analysis using Chi-Square test. The results of this study indicate that there is an influence between BPJS Health patient perceptions of patient satisfaction based on the responsiveness dimension with p value 0.001< 0.05, reliability p value 0.002 < 0.05, assurance p value 0.008 < 0.05, empathy p value 0.002 < 0.05. On the tangible dimension thereis no significant effect on patient satisfaction with a p value of 0.064 > 0.05. The variable that has the greatest influence on patient satisfaction is the responsiveness dimension with a p value (sig) of 0.001 < 0.05. The results of this study are the dimensions of responsiveness, reliability, assurance, empathy are variable that have an influence on patient satisfaction while tangible have no effect on patient satisfaction at Labuang Baji Hospital. It is suggested to the RSUD Labuang Baji to improve the quality of service and get a good perception from the patient.